LEGAL LIMITS ON THE RIGHT OF PRIVATE PROPERTY CONCERNING JUS ABUTENDI - MURZEA, Cristinel Ioan; MATEFI, Roxana (International Journal of Legal and Social Order, 2022)
This article proposes an analysis of the limits of private property rights. They do not limit the property right, but they temporarily limit one of its essential attributes - ius abutendi - which can have as its source either the will of the party or the will of the legislator expressed in the content of the normative act.